2012
DOI: 10.3748/wjg.v18.i16.1968
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial of transnasal ileus tube vs nasogastric tube for adhesive small bowel obstruction

Abstract: Ileus tube can be used for adhesive small bowel obstruction. Endoscopic placement of the ileus tube is convenient and worthy to be promoted despite the potential risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
47
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 19 publications
4
47
0
2
Order By: Relevance
“…Gastrointestinal decompression using an ileus tube or a nasogastric tube is considered to be an effective treatment in such patients [2]. A previous randomized controlled trial showed that the relief of clinical symptoms and improvement in the findings of abdominal radiography were quicker with an ileus tube than with a nasogastric tube [3]. Therefore, gastrointestinal decompression using an ileus tube is the first treatment choice in patients with ASBO at our hospital.…”
Section: Introductionmentioning
confidence: 97%
“…Gastrointestinal decompression using an ileus tube or a nasogastric tube is considered to be an effective treatment in such patients [2]. A previous randomized controlled trial showed that the relief of clinical symptoms and improvement in the findings of abdominal radiography were quicker with an ileus tube than with a nasogastric tube [3]. Therefore, gastrointestinal decompression using an ileus tube is the first treatment choice in patients with ASBO at our hospital.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, there have been reports from many countries describing the usefulness of LT decompression for the management of SBO. [1–4,68] Therefore, if the clinical course after NGT insertion is not satisfactory, we have to consider inserting the LT instead.…”
Section: Introductionmentioning
confidence: 99%
“…Small bowel obstruction (SBO) is usually caused by postoperative adhesions that develop in about 95% of adult patients after abdominal surgery . Some recent studies have shown that long transnasal tube decompression achieves favorable outcomes . We herein report a new effective transnasal ileus tube insertion method called the anterior balloon method to achieve decompression for adhesive SBO …”
mentioning
confidence: 99%